Martensitic formation and internal friction - Dogan, Ali (My University, 1992)
Coherent phonons which start martensitic formation are the solutions of the Duffing equation. By using this idea the frictional force was included in this undamped nonlinear equation. Numerical results were obtained for Au-Cu-Zn (30 at% Cu, 47 at% Zn) and In-Tl (21 at% Tl) single crystal. Dependence of vibrational amplitude of the phonons on frequency of driving force was researched for various temperatures in the austenitic range. It was found that damping effects change that strongly as the martensitic transformation temperature, Ms, is approached. The proposed model in this study can explain the jump phenomenon in the response curves more clearly and realistically when damping is included. © 1992 Akadémiai Kiadó.